Primary Aortoduodenal Fistula: First you Should Suspect it - Beuran,Mircea (2016)
ABSTRACT A 59 year-old patient was admitted with upper gastrointestinal bleeding. The clinical exam showed mild hypotension and blood samples revealed acute anemia (hemoglobin = 7.5 g/dl). Emergency computed tomography showed an infrarenal abdominal aortic aneurysm and extravasation of the arterial contrast material toward the digestive tract. The patient was transported to the operating room for emergency laparotomy, which showed an aortoduodenal fistula. After proximal and distal aortic vascular control, the two anatomical structures were dissected with duodenorrhaphy, patch repair of the aortic tear and omentum interposition. The postoperative recovery was uneventful, with discharge after 12 days.